2009
DOI: 10.1111/j.1471-4159.2009.06362.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases inhibition provides neuroprotection against hypoxia‐ischemia in the developing brain

Abstract: Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases which are capable of degrading many types of extracellular matrix proteins and involved in the process of tissue remodeling in various pathologic conditions, including inflammatory diseases, tumor cell invasion, and angiogenesis. Previous studies suggest that MMPs, in particular MMP-2 and MMP-9, are deleterious in the brain after stroke (Power et al. 2003;Svedin et al. 2007). In acute stage after ischemic stroke, the effect of MMP activity is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 33 publications
1
89
0
1
Order By: Relevance
“…Furthermore, a significant DOX effect was noted for platform jumping, with the sensitivity of placebo-pelleted C57 mice to acute morphine being reduced after DOX administration. It is possible that chronic morphine-induced inflammatory effects, such as increases in IL-1b or other cytokines (Liu et al, 2011;Merighi et al, 2013) might be reduced by DOX itself because DOX is reported to have modest anti-inflammatory effects at high doses (Chen et al, 2009;Chaudhry et al, 2010). Further, DOX increased the ED 50 on the %MPE in the tail-flick assay for all morphine-pelleted groups (no increase was noted in placebopelleted mice).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a significant DOX effect was noted for platform jumping, with the sensitivity of placebo-pelleted C57 mice to acute morphine being reduced after DOX administration. It is possible that chronic morphine-induced inflammatory effects, such as increases in IL-1b or other cytokines (Liu et al, 2011;Merighi et al, 2013) might be reduced by DOX itself because DOX is reported to have modest anti-inflammatory effects at high doses (Chen et al, 2009;Chaudhry et al, 2010). Further, DOX increased the ED 50 on the %MPE in the tail-flick assay for all morphine-pelleted groups (no increase was noted in placebopelleted mice).…”
Section: Discussionmentioning
confidence: 98%
“…This balance between the two molecules is thought to reduce brain damage in HI events by protecting the blood-brain barrier (7). MMP inhibition provides neuroprotection against HI in the developing brain (21). A neuroprotective role for TIMP-1 in excitotoxic damage and ischemia has been previously proposed (10,11,22).…”
Section: Mmp-9/timp-1 In Perinatal Brain Injurymentioning
confidence: 99%
“…For the endothelium, much in vivo evidence exists to support a role for MMP-mediated occludin proteolysis, particularly during blood-brain barrier (BBB) pathologies. Rodent models of cerebral ischemic injury, for example, demonstrate elevated levels of MMP-2/9 leading to occludin fragmentation in brain microvessels, with resultant elevated leakage and brain edema (13,20,64,114,128). Yang et al (128) went on to describe the temporal dynamics of these events, confirming that constitutively active MMP-2 is responsible for occludin cleavage and TJ "loosening" during the early transient phase of the ischemia (3 h), while MMP-9 and other products of extended neuroinflammation and reperfusion injury (e.g., reactive oxygen species) cause further occludin degradation and more long-term (24-h) alterations to BBB integrity.…”
Section: Proteolytic Degradation (I) Mmp-dependent Proteolysismentioning
confidence: 99%